Hubungan antara pH Susu dengan Jumlah Sel Somatik Sebagai Parameter Mastitis Subklinik - M Sudarwanto; E Sudarnika (Faculty of Animal Science, Bogor Agricultural University, 2008)
The aim of this research was to measure the relationship of the pH value to the somatic cell count as a parameter of sub clinical mastitis detection. Two hundreds quarter milk samples were used in this research and the test (the pH value, IPB-1 mastitis test and Breed method) was done in parallel way. The results showed that 152 samples from 200 samples (76%) tested with Breed method came from the herds which suffered from sub-clinical mastitis and with IPB-1 test showed that 145 (72.5%) of the samples had positive reaction. Using pH meter, it showed that 44 samples (22 %) had pH > 6.75, presumed suffered from sub-clinical mastitis and 2 samples (1%) showed pH < 6.30 (6.25 and 6.28). At the same time, these two samples showed a negative reaction with IPB-1 test and had somatic cell count of 360,000/ml and 280,000/ml, each. It also showed that there was a close relationship between pH value and IPB-1 test. The conclusion of this research was that the measurement of pH value was not a sensitive method for detecting sub-clinical mastitis. Key words: sub-clinical mastitis, pH, somatic cell count, IPB-1 mastitis test